Mechanical degradation of biomass wood pellets during long term stockpile storage - Graham, Shalini; Eastwick, Carol; Snape, Colin; Quick, Will (Elsevier, 2017)
This paper quantifies and assesses the mechanical degradation of white wood and steam exploded wood pellets in indoor and outdoor stockpile storage over a twenty-one month period in the UK. The indoor stored steam exploded wood pellets on the surface of the pile only exhibited a 3% decrease in durability after twenty months in storage. The outdoor stored pellets demonstrated much higher levels of mechanical degradation. In the summer period with high relative humidity and temperature, the durability of pellets sampled from the surface of the pile dropped from 92 to 22% after three months in storage with a durability of 10% measured after nine months in storage. The degradation of the pellets from the middle of the pile was more gradual and less severe with a maximum durability drop of 34%. The impact on mechanical properties was significant for the indoor stored white wood pellets with pellets quickly degrading to dust. This study shows that while steam exploded pellets could be stored in covered storage, white wood pellets require a fully enclosed storage environment. Short term outdoor storage of steam exploded pellets could be considered if extended periods of low rainfall and relative humidity can be reliably predicted.